Feeding habits of juvenile Trematomus newnesi (Pisces, Nototheniidae) at Potter Cove, South Shetland Islands, Antarctica - Barrera Oro, Esteban; Piacentino, Gabriela Laura Maria (Polar Biology)
The dietary composition of juvenile Trematomus newnesi, trawled at Potter Cove, South Shetland Islands, in the summers 2004–2005 and 2005–2006 was analysed using frequency of occurrence (F%) and dietary coeYcient Q (%) methods. The samples consisted exclusively of immature specimens in the range 4– 15.4 cm (total length) and are complementary to those of larger Wsh from the same site, including adults, which were analysed in previous work. Benthic-demersal organisms such as gammaridean amphipods and harpacticoid copepods were the main (coeYcient Q) and most frequent (F%) prey. The importance of the smaller and larger main prey diminished and increased, respectively, during ontogeny. Pelagic krill, being negligible in the diet of the small and medium size Wsh categories, became secondary food, but only for Wsh larger than 12 cm. Other taxonomic groups occurred scarcely and constituted occasional food. They were mostly benthic, such as gastropods, bivalves, isopods, cumaceans, and algae, with the exception of an insigniWcant number of pelagic ostracods and calanoid copepods. Unlike the more pelagic/planktivorous mode of life known for late juvenile-adult stages of T. newnesi, including cryopelagy, present results indicate that early juvenile Wsh remain sheltered among macroalgae beds preying on the associated community of demersal-benthic organisms. Fil: Barrera Oro, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Piacentino, Gabriela Laura Maria. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina